Robots and drones : past, present, and future - Scott, Mairghread (Science comics (First Second (Firm)), 2018)
Presents a series of comics showcasing real robot and drone technology in the modern world, from tea-serving machines dating back to feudal Japan up to modern NASA rovers on Mars.